Women’s movement and media representation in contemporary Iran - Kobra, Mohammadpour Kachalami (2019)
The Iranian political system oppresses Iranian women by legislating gender discriminatory laws, oppressive representation of women in media particularly Iran’s national television (TV) network and repressing the Iranian women’s movement by restricting public activities, jailing, and sentencing their activists. This study was guided by three research questions: 1) What is the current state (2015 and early 2016) of women movement in Iran/ in the context of Iranian political system? 2) How do Iranian women’s movement activists view gender representation in the media through critical analysis? 3) How do the Iranian women’s movement activists discern the influence of Iran’s national TV programs on further oppression of women? The study deployed critical media literacy framework which focuses on politics of representation and ideology critique. The theory helps refine and construct research questions, guide research processes, select research method, and analyze data and findings. A qualitative approach was used to address the research questions. Based on purposive and snowball sampling techniques, fifteen Iranian women’s movement activists voluntarily participated. The data were collected through face to face and semistructured interviews. The data derived from transcripts of the interviews were analyzed through coding and categorizing into themes. The findings reveal that the Iranian women’s movement has been severely oppressed by Iran’s political system since a major protest during the 2013 presidential election. Despite this oppression and periods of silence the movement will revive itself. The most significant obstacle to developing an Iranian women’s movement is oppression by the political system. Iranian women’s movement activists fight for many women’s issues, including violence against women, discriminatory laws and political participation. The activists use media for struggle against gender discrimination, particularly the Internet and social media as it is more accessible in the current repressive state. Iranian women movement’s activists discern structures of gender oppression in media representation and understand how Iranian national TV tries to naturalize and reinforce patriarchy and sexism through its TV series and commercials. Drawing on core concepts of critical media literacy, the findings of this study demonstrate that the politics of representation with a focus on sexist ideology are the most prominent concepts considered by Iranian women’s movement activists. Furthermore, they discern other core concepts of critical media literacy except recognizing media languages and representation techniques. The study concludes that the major reason why the Iranian women movement has declined in recent years is due to the increasing suppression by the state-Islamic system since 2013. One technique used to suppress the movement is the way Iran’s national TV and mainstream media tries to reinforce patriarchy and sexism through its portrayal of women in many TV series and commercials. Through critical analysis of media messages, the Iranian women’s movement activists not only resist media manipulation and women oppression, but also participate in political movements struggling for transformation of oppressive gender politics of the Islamic Republic of Iran through the accessible Internet and new media.